Life-Cycle environmental impact assessment of primary beverage containers: glass versus plastic bottles - Bonilla Toribio, Diego (2024)
Pollution originating from the life cycle of packaging is increasing and can have potentially irreversible consequences for the environment. In the beverage industry, the most common materials used for the production of primary packaging are glass and plastic. The objective of this study was to compare the environmental impacts of polyethylene terephthalate and glass bottles. The Leopold Matrix was applied to evaluate the environmental impact of the life cycle of both bottles, using information from a wide range of scientific articles and peer-reviewed indexed journals. The evaluation took into account the abiotic, biotic, and anthropic components generating negative consequences for ecosystems, human health, and fauna and flora. The study found that both containers generate negative environmental impacts throughout their life cycle. This was evidenced in the results of the matrix, where the total values symbolize –712 and –690 for glass and plastic, respectively.